GAMBARAN PROFESSIONAL QUALITY OF LIFE (PROQOL) GURU ANAK BERKEBUTUHAN KHUSUS - Purnamasari, Dewa Ayu Inten; Satyadi, Heryanti; Rostiana, Rostiana (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
Professional Quality of Life (ProQOL) is a topic that has been growing for the last 20 years. Stamm is an expert who is developing theoretical concepts and its instrument in 2010. ProQOL explains individual’s perceptions professional quality of life, which consists of two aspects. Compassion Satisfaction (CS) is the positive aspect where someone is able to feel positive feelings such as altruism while working and Compassion Fatigue (CF) is the negative ones, where someone feels uncomfortable which can leads to Burnout and Secondary Traumatic Stress (STS) symptoms. Most of study has investigated ProQOL among health caring professional, therefore this study aims to overview ProQOL among special education teachers. Uses quantitative-non experimental design, this study involves 171 special education teachers as participants. Based on the collected data, it shows that individual’s perceptions about the quality of life as a special education teacher tends to be positive. However, this is not necessarily followed by low STS and burnout rates. This study found that around 77% teachers were at moderate to high burnout levels, while 72% also had moderate to high STS levels. Professional Quality of Life (ProQOL) merupakan sebuah topik yang sudah berkembang sejak 20 tahun terakhir. Seorang ahli bernama Stamm telah berjasa dalam mengembangkan konsep teoretis ProQOL beserta alat ukurnya pada tahun 2010. ProQOL menjelaskan persepsi individu mengenai kualitas hidup profesionalnya, yang terdiri dari dua aspek. Compassion Satisfaction (CS) merupakan aspek positif dimana individu mampu merasakan perasaan positif, altruisme terkait perkerjaannya dan Compassion Fatigue (CF) yang merupakan aspek negatif, dimana individu merasa tidak nyaman dalam menjalankan pekerjaannya yang berujung pada gejala Burnout dan Secondary Traumatic Stress (STS). Oleh karena sebagian besar penelitian mengenai ProQOL telah diteliti pada tenaga profesional kesehatan, penelitian ini bertujuan untuk memperoleh gambaran ProQOL pada profesi guru ABK. Penelitian ini merupakan penelitian kuantitatif non-eksperimental yang melibatkan 171 guru ABK sebagai partisipan. Berdasarkan data yang terkumpul diperoleh bahwa persepsi individu terhadap kualitas hidup profesional sebagai guru ABK cenderung positif. Akan tetapi, hal tersebut tidak serta merta diikuti dengan tingkat burnout dan STS yang rendah. Berdasarkan hasil penelitian, sekitar 77% guru ABK berada pada tingkat burnout Sedang-Tinggi dan 72% diantaranya juga memiliki tingkat STS Sedang-Tinggi.